Paul the Jew : rereading the apostle as a figure of Second Temple Judaism - Boccaccini, Gabriele, 1958-; Segovia, Carlos A., 1970-; Doody, Cameron J. (Minneapolis, Fortress Press, 2016)
"The decades-long effort to understand the apostle Paul within his Jewish context is now firmly established in scholarship. The latest fruit of sustained analysis appears in the essays gathered here, from leading international scholars who take account of current investigations into the scope and variety present in Second Temple Judaism. Contributors address broad historical questions as well as questions about interpretation itself, including the extent and direction of a "paradigm shift" in Pauline studies and the evaluation of the Pauline legacy."--Page 4 of cover
The three paths to salvation of Paul the Jew / Gabriele Boccaccini (with responses by Albert I. Baumgarten and Daniel Boyarin) -- Who is the righteous remnant in Romans 9-11? : the concept of remnant in early Jewish literature and Paul's Letter to the Romans / Shayna Sheinfeld -- The "historical Paul" and the Paul of Acts : which is more Jewish?
"Most of the chapters that follow were offered first as papers at the Third Nangeroni Meeting of the Enoch Seminar ... which was held at the Valdensian Faculty of Theology (Rome) in June 2014"--Preface, page xi
Includes bibliographical references and index
Keywords: Paul, -- the Apostle, Saint -- Congresses; Conference papers and proceedings